Biological Oxidations and Antioxidant Activity of Natural Products - Nunes, Xirley Pereira; Silva, Fabrício Souza; Almeida, Jackson Roberto Guedes da S.; Lima, Julianeli Tolentino de; Ribeiro, Luciano Augusto de Araújo; Júnior, Lucindo José Quintans; Filho, José Maria Barbosa (IntechOpen, 2012)
None